Search for the lepton flavor violating decay Z→eμ in pp collisions at s√ TeV with the ATLAS detector - Onofre, A. (2014)
The ATLAS detector at the Large Hadron Collider is used to search for the lepton flavor violating process Z → eμ in pp collisions using 20.3 fb−1 of data collected at ffiffiffi s p ¼ 8 TeV. An enhancement in the eμ invariant mass spectrum is searched for at the Z-boson mass. The number of Z bosons produced in the data sample is estimated using events of similar topology, Z → ee and μμ, significantly reducing the systematic uncertainty in the measurement. There is no evidence of an enhancement at the Z-boson mass, resulting in an upper limit on the branching fraction, BðZ → eμÞ < 7.5 × 10−7 at the 95% confidence level.